Characterization of SrCO 3 and BaCO 3 nanoparticles synthesized by cyclic microwave radiation - Narongrit Tipcompor (2018)
Uniform strontium carbonate (SrCO3) and barium carbonate (BaCO3) nanoparticles were successfully synthesized using alkaline earth metal nitrate (M(NO3)2with M2=Sr2and Ba2) and sodium carbonate (Na2CO3) in ethylene glycol by a cyclic microwave radiation. The products were characterized by X-ray powder diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM) and selected area electron diffraction (SAED). In this research, the products were orthorhombic SrCO3and BaCO3phase with nanoparticles over the ranges of 20-50 nm for SrCO3and 40-100 nm for BaCO3, including the detection of asymmetric C-O stretching, symmetric C-O stretching, out of plane bending and in plane bending vibrations at 1463, 1071, 862 and 708 cm-1for SrCO3, and 1439, 1059, 858 and 692 cm-1for BaCO3, respectively. © 2012 Elsevier B.V.